A Comprehensive Geospatial Analysis for Optimal Waste Disposal Site Selection: Integrating Environmental, Social and Economic Factors - Chauhan, Jenish; Ghimire, Subash (Kathmandu University Journal of Science, Engineering and Technology, 2023)
Uncontrolled city growth and quick development have made solid waste management a global challenge. Choosing the wrong disposal site leads to economic, physical, and environmental losses, impacting the human environment deeply. The aim of this paper is to discuss on geospatial analysis for optimal waste disposal site selection integrating environmental, social and economic factors. Among various methods, the combination of Geographic Information System (GIS) and Analytical Hierarchy Process (AHP) based on Multi Criteria Decision Analysis (MCDA) has proven to be a good way to find suitable landfill sites. This paper also presents the selection of the best and most scientific landfill sites within Kavrepalanchowk District of Nepal. In this study, seven criteria are taken into account: distance to water bodies, distance to road, and distance to settlement area, slope percentage, soil type, geology, and forests. Each rating map is created using GIS environment and the weight is obtained from the AHP pairwise comparison matrix. The map showing suitable sites for waste disposal is obtained by using the weightage overlay tool and assigning the weightage to each criterion.